Structural layout that takes full advantage of the capabilities and opportunities afforded by two-way RC floors, coupled with the selection of the best technique, to avoid serviceability failures. (December 2016) - Foraboschi, Paolo
Abstract: A recently cast two-way rectangular reinforced concrete floor with a span-to-thickness ratio equal to 34.1, which constituted the two stories above ground of an office building under construction, exhibited a totally unsatisfactory deflection performance. The static loading test performed at the end of the construction work demonstrated that the stiffness of the floor was too low. Furthermore, not only the floor that had been loaded for the test, but also the other floor, exhibited excessive increases in deflections with time. The author was entrusted with the task of redesigning the floor, which had to constitute the stories of a further nine buildings of the construction lot, whose floors had been designed equal to the floor that had failed, and neither the spans nor the thickness could be changed. The author designed and constructed a test building whose story was made up of a floor with perimeter, spans and thickness equal to those of the floors that had failed, but with different structural conformation, boundary conditions, and both amount and configuration of steel reinforcement. The new floor was built using a different construction method as well. The loading test carried out on this floor measured very low immediate deflections. The load was left on the floor for three years and the deflections increased only moderately. The test results substantiated all the theoretical analyses that had been previously carried out and confirmed that the structural performance was adequate. On that account, the proposed floor was eventually employed for the nine buildings of the complex that remained to be built. This paper – which is directed at analyzing a structural failure, helping reduce the incidence of serviceability failures, and extending the operating horizons of thin RC floors – explains why the original version of the floor failed, describes the new version of the floor, including the loading test on the prototype and on the nine new buildings, and provides a useable and reproducible recipe for designing and assessing high span-to-thickness ratio rectangular RC floors. Graphical abstract: Highlights: Serviceability failure of RC floors and beams due to inaccurate deflection predictions Taking advantage of capabilities and opportunities of two-way structures even though rectangular Minimizing the effects played by cracking and creep in deflections and preventing failure Criteria and practice to design two-way rectangular RC floors with high span-to-thickness ratios Field test procedures undertaken to assess the proposed floor and to disentangle design from modeling